Inductive algebras for the affine group of a finite field - Sharma, Promod; Vemuri M.K. (Springer Science and Business Media Deutschland GmbH, 2022)
Each irreducible representation of the affine group of a finite field has a unique maximal inductive algebra, and it is self-adjoint.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Affine group; Affine group; Induced representation; Inductive algebra